Studi Konten Analisis : Analisis Kecenderungan Dan Tren Riset Pendidikan Untuk Mata Pelajaran Fisika Di Indonesia - Rosa Safirotun Nabilah; Jumadi Jumadi (Jurnal Penelitian Pendidikan IPA, 2022)
Physics educational research trends are always changing from time to time. This change follows the phenomenon of educational problems that are developing in the field. The current study is a content analysis of research to analyze the trends of physics educational research that was published between the years of 2018 and 2021, visualize physics educational research trends and how Indonesian researchers contribute to physics educational research. This research was reached through the Journal of Research in Science Education (JPPIPA). Data obtained is 48 data and taken with "physics education" as the keyword. It is aimed to guide the researchers who are planning to conduct studies in this particular field by specifying physics education in terms of their methods, subject areas, research titles, data analysis techniques, and sampling types. Based on the results of the research that has been carried out, it can be concluded that the trend of educational research has increased and is in great demand by researchers in 2021. The physics material that is the research trend is wave material. The subject variable that is often studied is research in the cognitive domain. The trend of physics education research tends to be research that uses quantitative research methods with quasi-experimental design and uses data collection instruments in the form of test instruments. The type of sampling used is school students both junior and senior high school. The trend of physics education research also tends to quantitative descriptive research with data analysis techniques using frequencies, percentages, and charts. Number author or authors are becoming a trend in physics education research as much as three and the number of research references are often used as reference only 1-30. The results of this analytical research can be used to guide and provide references for research that will be carried out by further researchers, especially in the field of physics education research